Pretesting survey questionnaire: a guide on dissemination - Hashim, Sabrina; Mohamad, Siti Fatimah; Abdul Halim Lim, Sarina; Che Ahmat, Nur Hidayah (Human Resource Management Academic Research Society, 2022)
A pretest is an integral aspect of a quantitative study as it highlights the improvisation needed to create effective survey questionnaires. It is important to administer a pretest to ensure the actual data collection can be properly conducted. This paper is part of ongoing research which describes the process of conducting a pretest through the distribution of survey questionnaires on an online platform. The pretest was conducted on hospitality and tourism students from two private colleges in Klang Valley. Steps on the expert review to evaluate the validity of the instrument are discussed in detail. The challenges faced in selecting participants and establishing contact with the targeted population are described. This included overcoming communication issues which needed to be done online because of the pandemic restrictions which limits the possibility of physical meeting with the representative of the selected colleges to seek permission for the study to be conducted. This paper discusses the execution as well as findings from the pretest and the improvement done in developing an effective survey questionnaire.